PENINGKATAN KREATIVITAS ANAK MELALUI PERMAINAN KARTU GAMBAR ANAK USIA 4-5 THN PADA PUSAT PAUD RENGGANG KABUPATEN GOWA - Andi Rezky Nurhidayah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2020)
Abstract: Increasing Children's Creativity through Children's Picture Cards 4-5 Yrs at Renggang Paud Center, Gowa Regency. This research enhances children's creativity through picture card media in early childhood Renggang PAUD Center Gowa Regency. This type of research used in research using PTK classroom action research. The subjects of this class action research are students aged 4-5 years with a total of 12 children consisting of 7 boys and 5 girls. The data consists of tests, questionnaires or questionnaires, interviews, observations, multilevel scale, and documentation. The results of this study indicate an increase in the ability to recognize images by using a picture card media in early childhood in the Renggang PAUD Center Gowa Regency after learning. 2 children who began to develop or recognize the picture as much as 7%.